(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article were considered the classical theory of purchasing power parity (PPP), neoclassical theory of the currency exchange rate (theory of floating exchange rates, theory of normative exchange rate) and approaches in regulation of currency exchange rate. In addition, in the work was shown that the concept of the currency exchange rate have a long evolution, reflecting the development of the international monetary relations and effectiveness of monetary policy in Kazakhstan.